2011
DOI: 10.1007/s00251-011-0542-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mouse 129-strain Nkrp1-Clr gene cluster reveals conservation of genomic organization and functional receptor–ligand interactions despite significant allelic polymorphism

Abstract: The Nkrp1 (Klrb) family of NK cell receptors and their genetically linked Clr (Clec2) ligands are conserved between rodents and humans. Nonetheless, certain mouse and rat Nkrp1 genes exhibit significant allelic polymorphism between inbred strains. We previously demonstrated that the Nkrp1-Clr recognition system is genetically and functionally conserved between the B6 and BALB/c strains, with focused sequence divergence evident in certain genes (e.g., Nkrp1b,c). Here, we extend this finding by mapping the 129-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 37 publications
5
45
0
Order By: Relevance
“…12,17,18 The currently known receptor-ligand pairs for these families include NKR-P1B: Clr-b; NKR-P1F:Clr-c,d,g; and NKR-P1G:Clr-d,f,g. 17,18,21,22 We have generated an NKR-P1B-deficient B6 mouse strain to study the role of NKR-P1B in NK cell development and function in vivo. We chose to target NKR-P1B for the following reasons: (1) the NKR-P1B:Clr-b system is well characterized in mice, and appropriate reagents, such as specific monoclonal antibodies (mAbs) and a complementary Clr-b gene-deficient mouse strain, are available 13,23 ; (2) the NKR-P1B:Clr-b system is analogous to the inhibitory NKR-P1A:LLT1 system in humans, although their expression patterns may vary 24,25 ; (3) the existence of 3 significantly different Nkrp1b alleles suggests a possible divergence as a result of pathogen challenge (eg, rat cytomegalovirus encodes a C-type lectinlike protein with homology to rat Clr- 11 [Clec2d11] that protects infected cells from NK recognition via the inhibitory rat NKR-P1B receptor) 26 ; and (4) in contrast to other, tissue-specific Clr family members, Clr-b, like MHC-I, is broadly expressed on hematopoietic cells, and its expression on transfected cells protects them from NK-mediated lysis.…”
Section: B6mentioning
confidence: 99%
See 1 more Smart Citation
“…12,17,18 The currently known receptor-ligand pairs for these families include NKR-P1B: Clr-b; NKR-P1F:Clr-c,d,g; and NKR-P1G:Clr-d,f,g. 17,18,21,22 We have generated an NKR-P1B-deficient B6 mouse strain to study the role of NKR-P1B in NK cell development and function in vivo. We chose to target NKR-P1B for the following reasons: (1) the NKR-P1B:Clr-b system is well characterized in mice, and appropriate reagents, such as specific monoclonal antibodies (mAbs) and a complementary Clr-b gene-deficient mouse strain, are available 13,23 ; (2) the NKR-P1B:Clr-b system is analogous to the inhibitory NKR-P1A:LLT1 system in humans, although their expression patterns may vary 24,25 ; (3) the existence of 3 significantly different Nkrp1b alleles suggests a possible divergence as a result of pathogen challenge (eg, rat cytomegalovirus encodes a C-type lectinlike protein with homology to rat Clr- 11 [Clec2d11] that protects infected cells from NK recognition via the inhibitory rat NKR-P1B receptor) 26 ; and (4) in contrast to other, tissue-specific Clr family members, Clr-b, like MHC-I, is broadly expressed on hematopoietic cells, and its expression on transfected cells protects them from NK-mediated lysis.…”
Section: B6mentioning
confidence: 99%
“…Notably, NKR-P1G is another inhibitory member of the NKR-P1 receptor family, and NKR-P1F shares overlapping ligand specificity with NKR-P1G. 11,15,21,22,49 A full analysis of Clr-b interactions with other Clr family members remains to be tested.…”
Section: Role Of Nkr-p1b In Natural Killer Cell Function 2223mentioning
confidence: 99%
“…Yet to date, NKR-P1C, the prototypical NK1.1 antigen in B6 mice (Glimcher et al, 1977;Koo and Peppard, 1984;Ryan et al, 1992), and NKR-P1A remain orphan-activating receptors with unknown physiological ligands. On the other hand, the paired NKR-P1F and NKR-P1G receptors recognize overlapping ''self'' Clr (Clec2) ligands to balance signals during NK cell education and effector responses, while the inhibitory NKR-P1B receptor recognizes the broadly expressed self Clr-b (Clec2d) ligand (Carlyle et al, 2004;Chen et al, 2011;Iizuka et al, 2003;Kveberg et al, 2009 been shown to be involved in ''missing-self'' recognition under diverse pathological states (Kirkham and Carlyle, 2014), including cancer (Carlyle et al, 2004), genotoxic and cellular stress (Fine et al, 2010), hematopoietic transplantation , immune escape of primary lymphoma cells , and cytomegalovirus and poxvirus infection Voigt et al, 2007;Williams et al, 2012), while the remainder of the self Clr ligands remain less well characterized. Among pathogens recognized by NK cells, cytomegaloviruses (CMV) demonstrate co-evolution with their natural hosts, likely due to cycles of natural selection for viral versus host fitness.…”
Section: Natural Killer (Nk) Cells Are a Subset Of Innate Lymphoid Cementioning
confidence: 99%
“…Even though NKR-P1 receptors and their Clr ligands are less polymorphic than Ly49s and their MHC ligands, there are some allelic variations of both NKR-P1A and NKR-P1B [29]. Some alleles are so divergent they have mistakenly been characterized as novel proteins (rat NKR-P1B PVG as NKR-P1C [15], and mouse NKR-P1B B6 as NKR-P1D [30].…”
mentioning
confidence: 99%
“…Rat NKR-P1B is a strong inhibitory receptor that is expressed by a major subset of nonalloreactive Ly49 low NK cells [15], as well as by a characteristic subset of highly responsive, fully differentiated NK cells detected in larger numbers in peripheral blood, liver, and gut-associated lymphoid organs [27]. NKR-P1B is shown to be important for non-MHC-dependent "missing self"-recognition, and downregulation of ligand in response to virus infections and genotoxic stress induces increased sensitivity to NK-mediated killing by the loss of inhibitory signaling in the NK cell [17,28].Even though NKR-P1 receptors and their Clr ligands are less polymorphic than Ly49s and their MHC ligands, there are some allelic variations of both NKR-P1A and NKR-P1B [29]. Some alleles are so divergent they have mistakenly been characterized as novel proteins (rat NKR-P1B PVG as NKR-P1C [15], and mouse NKR-P1B B6 as NKR-P1D [30].…”
mentioning
confidence: 99%